Realizing both giant magnetic anisotropy and quantum anomalous Hall effect in graphene with adsorbed Te-Co dimer. (17th December 2018) - Zhang, Kai-Cheng; Li, Yong-Feng; Liu, Yong; Zhu, Yan
Abstract: To realize quantum anomalous Hall state at higher temperature, it needs to search for the magnetic topological insulators with giant magnetic anisotropy. We have studied the structural, magnetic and topological properties of graphene with adsorbed Te-A (A Co, Rh, Ir) dimers by first-principles calculations and Wannier technique. Our results reveal that the system of Te-Co@G is an excellent magnetic topological insulator with both perpendicular magnetic anisotropy of 61.7 meV and large topological band-gap of 35.8 meV. Both the magnetic anisotropy and the band-gap can be effectively tuned by the applied electric field. The dimers are stably adsorbed onto the graphene and the systems are robust against thermal fluctuation. Topological analysis reveals that the adsorption system is the Chern insulator with .